A novel Zigbee-based data acquisition system for distributed photovoltaic generation in smart grid - Zahurul S.; Mariun N.; Kah L.; Hizam H.; Othman M.L.; Abidin I.Z.; Norman Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data acquisition; Database systems; Digital storage; Electric power transmission networks; Photovoltaic cells; Windows operating system; Wireless networks; Wireless telecommunication systems; Zigbee; AC electrical parameters; Communication technologies; Microsoft Access database; Photovoltaic generation; Photovoltaic modules; Smart grid; Wireless data acquisitions; Zigbee wireless technologies; Smart power grids